HMGB1: the missing link between diabetes mellitus and heart failure - Volz, Hans Christian; Seidel, Cathrin; Laohachewin, Danai; Kaya, Ziya; Müller, Oliver J.; Pleger, Sven Torsten; Lasitschka, Felix; Bianchi, Marco E.; Remppis, Bjoern-Andrew; Bierhaus, Angelika; Katus, Hugo; Andrassy, Martin (Basic research in cardiology, 2010)
Diabetes mellitus (DM) is a major independent risk factor for cardiovascular disease, but also leads to cardiomyopathy. However, the etiology of the cardiac disease is unknown. Therefore, the aim of this study was to identify molecular mechanisms underlying diabetic heart disease...